Fenomenologi Kepuasan Konsumen dalam Menggunakan Layanan E-Commerce TikTok Shop - Aji, Nahrowi Taju; Ernajati, Justia (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2025)
This study aims to explore the experiences of university students in using the TikTok Shop e-commerce platform and to identify the factors that influence their satisfaction. The research employs a qualitative phenomenological approach, using data collection techniques such as participatory observation, semi-structured interviews, and documentation. The findings reveal that student satisfaction is influenced by the ease of app access, engaging interactive features such as live shopping, service speed, and the level of trust in the platform. The study also found that some students experienced dissatisfaction due to delivery delays and products not matching expectations. Based on these results, it can be concluded that although the majority of students are satisfied with using TikTok Shop, there are still several service aspects that require improvement. This research provides valuable insights into digital consumer behavior and serves as a foundation for developing more responsive e-commerce service strategies that align with the needs of young users.